Ante-Bellum reform. Ed. by D. Brion Davis [With contribs of R.W. Emerson, A. Craven, M.A. Duberman a.o.] (Harper & Row, 1967)
With bibliogr. Interpretations of American history. Editors: J. Higham and B. Perkins.